Sanctus: An Architecture for Trusted Products - Shore, Malcolm; Zeadally, Sherali; Clark, Andy (Journal of Telecommunications and the Digital Economy, 2019)
The last two decades have seen a fundamental shift in the manufacturing, sourcing and operation of technology, which has raised concerns in state security agencies about the cybersecurity risk to government and critical infrastructure. Sophisticated cyber attacks continue to be launched by state actors worldwide, while the engineering practices in common use have failed to deliver a commensurate improvement in technology cyber security. Cyber attacks continue to be successful against commercial networks, leading the US Government to encourage government agencies to look towards models such as zero-trust networking and tailored trustworthy spaces. There has been progress in product engineering, with formal methodologies such as Correctness by Construction (CbyC) successfully producing commercial products with increased trustworthiness. However, the adoption of these techniques has been limited, and governments are now increasingly resorting to an approach of technology Balkanization, where import and use of products and components may be restricted based on their country of origin. Even in the early stages of this strategy, the effect upon the economy is significantly adverse. We propose an alternative to technology Balkanization by combining trustworthy engineering approaches with the use of a national security component we call a sanctum which together can deliver sovereign trust.